Reaksi Pasar atas Pengumuman Pemecahan Saham pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Dewanata, Ngakan Putu Wahyu Pandu; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2021)
This study aims to examine the market reaction caused by the announcement of the stock split. The population used in this study amounted to 67 companies. The method used in sampling using saturated samples, using the entire company that did the stock split. The data obtained is secondary data consisting of stock prices, IHSG, and stock trading volume. In analyzing the data, this study used the One-Sample T-Test and Paired Sample T-Test. The results showed that  there was a market reaction to the announcement of a stock split as indicated by an abnormal return, there was a market reaction to the announcement of a stock split as indicated by the volume of stock trading, there is no difference in markets reaction before and after the announcement of the stock split. Keywords: Stock Split; Abnormal Return ; Stock Liquidity.